Dinamika Metode Pembelajaran Bahasa Arab - Mustafa Mustafa (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2020)
The method is one of the very important components of learning Arabic. It cannot be denied that the existence of methods greatly influences learning. One of the success factors of a learning process is a good method. The method is certainly supported by the competence of an educator in carrying it out. This paper aims to convey the dynamics of learning methods in a comprehensive manner. Some classical and modern methods that cannot be separated from learning Arabic, that is grammar and translation method, direct method, reading method, audio-lingual method. All of these methods are still quite relevant to learning Arabic in the contemporary context. Learning Arabic cannot be separated from the translation process with the appropriate language rules. The same is true for the direct method, reading dan practice of listening and speaking the language.